Feasibility Study of Implementing an Internet of Things (IoT) Project at Milad Hospital, Tehran - Mohammadreza Zahedi; Seyyed Mahdi Hosseini Sarkhosh (Tehran University of Medical Sciences, 2023)
Background and purpose: The Internet of Things (IoT) essentially refers to the connectivity of various objects through the internet to facilitate a more efficient and intelligent experience. However, due to the emerging nature of this technology in Iran, instances of its full deployment in service organizations, including hospitals, are rare or infrequent. Therefore, the aim of this study is to identify the key success factors for the deployment of IoT and assess the readiness for implementing this technology in Milad Hospital, Tehran. Methods: This research is a descriptive-survey study conducted in two phases. In the first phase, 30 key success factors were identified through a review of previous studies. In the second, survey phase, 93 managers and staff members of Milad Hospital formed the statistical population, and data was collected through a researcher-made questionnaire. The comparison of the current and ideal states of success factors for IoT implementation, and their ranking, were done using the t-test and Friedman test in SPSS software. Results: Based on this study, factors such as information technology, organizational culture, organizational structure, and human resources were identified as the most crucial for successful IoT deployment in the hospital. Additionally, the results showed that there is a significant gap between the hospital's current state and the desired state for IoT implementation in these identified areas. Conclusion: Successful implementation of IoT requires enhancement in readiness, both in terms of technological and organizational-cultural infrastructures